Integrating STEM-Based Learning to Improve Critical Thinking Skills Among Elementary School Students - Andini Rahmawati (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
The development of critical thinking skills is essential for preparing future generations to effectively navigate the challenges posed by rapid technological and scientific advancements. This study examines the effectiveness of STEM-based learning (Science, Technology, Engineering, and Mathematics) in enhancing critical thinking skills among elementary school students in Indonesia. Using a quasi-experimental method with a pre-test and post-test control group design, this research involved 120 students from three elementary schools in East Java. The experimental group was taught using an integrated STEM approach, while the control group continued with a traditional curriculum. The primary objective was to assess how STEM-based learning impacts students' critical thinking, particularly in areas such as problem-solving, reasoning, and analysis. The results revealed a significant improvement in the critical thinking abilities of students in the STEM group compared to the control group. Students in the experimental group demonstrated enhanced skills in problem-solving and reasoning, with notable improvements in their ability to analyze and evaluate information. Additionally, the STEM group exhibited higher levels of engagement, curiosity, and motivation in their learning, along with a greater ability to apply interdisciplinary knowledge to real-life contexts. These findings suggest that STEM-based learning can play a crucial role in developing critical thinking and other essential skills required in the 21st century. This research underscores the potential benefits of incorporating STEM education into elementary school curricula to foster critical thinking and prepare students for future challenges. The study recommends that policymakers and educators focus on providing the necessary training, resources, and support to effectively implement STEM-based learning in primary education. By doing so, we can ensure that students develop the skills needed to succeed in a rapidly evolving world.